Efektivitas Teknik Counterpressure Terhadap Penurunan Tingkat Nyeri Pada Persalinan - Silfi Rohmaniyah; Farida yuliani; Fitria Edni Wari; Nurun Ayati Khasanah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2026)
Labor pain primarily arises from uterine contractions that activate the sympathetic nervous system, leading to changes in blood pressure, heart rate, and breathing patterns. When not managed properly, this pain may intensify anxiety, tension, fear, and psychological stress. This study aimed to examine the effect of counterpressure massage in reducing labor pain. This quantitative research used an experimental approach with a pre-experimental one-group pretest–posttest design. The study was conducted at Petrokimia Gresik Hospital. The population consisted of all women who delivered at the hospital during January–February 2025. Using accidental sampling, 40 respondents were recruited. The independent variable was the administration of counterpressure massage during the first stage of labor, while the dependent variable was the reduction of pain in the first stage of labor. Data were analyzed using SPSS, and the Wilcoxon test was applied for statistical testing. The study took place from January to February 2025. Results indicated that before receiving counterpressure massage, most respondents reported severe pain (27 participants; 67.5%). After the intervention, the majority experienced moderate pain (22 participants; 55%). Statistical analysis showed that counterpressure massage significantly reduced labor pain at Petrokimia Gresik Hospital (p = 0.000, p < 0.05). These findings suggest that counterpressure massage meaningfully lowers pain intensity during labor, helping the delivery process proceed more smoothly and with fewer complications. Therefore, incorporating counterpressure massage into an official standard operating procedure (SOP) in the delivery room is recommended as a formal pain-reduction measure, so that laboring mothers experience less anxiety and tension and a decreased perception of pain